Financial Ratio Analysis that Distinguishes Company Shares Indexed in LQ45 and the Non-LQ45 on the Indonesia Stock Exchange (Bursa Efek Indonesia) - Nugroho, Mulyanto Nugroho (Archives of Business Research, 2018)
The LQ45 index is the rank 45 ranking of the most liquid listed companies in the Indonesia Stock Exchange (BEI). By being in the LQ45 index, the company will be smoother in long-term funding because the shares circulating in the market tend to be more attractive if they are on the LQ45 index. This can be seen on the listing board for market activity published on the Indonesia Stock Exchange (BEI) website (www.idx.com). LQ45 companies tend to have high frequency of transaction values. To be indexed in LQ45, the Indonesia Stock Exchange does not specify how the financial conditions are the criteria of an LQ45 company. This study tries to look at the criteria of LQ45 companies through aspects of financial conditions. This is done by analyzing financial ratios in LQ45 companies and compare them with non-LQ45 companies with the same sector. In this research was using 6 financial ratio with 25 financial ratio indicators. The number of samples in this study amounted to 230 companies then they are divided into 35 sample companies in the category of LQ45 companies and 195 companies in the category of non-LQ45 companies with the same sector. From discriminant analysis, the results of analysis can show whether there is a significant difference or not between the company’s ROC indexed LQ45 and non-LQ45. The results output can be used as criteria for aspects of the financial situation that need to be observed by corporate stakeholders. The test results through discriminant analysis prove that there is a significant difference between LQ45 indexed company financial ratios and firms that are not indexed in LQ45 (non-LQ45). The results also prove that variables capable of distinguishing between companies indexed by LQ45 and those that are non-LQ45 from the 25 variables tested in this study include the dividend yield ratio (DYR), total assets turnover (TAT), per-share dividend (DPS), net working capital (NWC), market book value per share (MBVP), debt to equity ratio (DER), current ratio (CURRENT R), long term debt to equity (LTDE), account receivable turnover (ARTO ), operating profit margin (OPM), fixed assets turnover (FAT), and inventory turnover (ITO). The most significant variable that distinguishes between indexed company financial ratio in the LQ45 index and companies not listed on the LQ45 index is dividend yield ratio (DYR).